(untitled) (Panacea Journal of Medical Sciences, 2024)
Artificial Intelligence (AI) and Machine Learning (ML) are revolutionizing healthcare by improving patient outcomes, enhancing diagnostics, and optimizing clinical workflows. AI-powered systems are increasingly being adopted to assist in diagnostics, personalized medicine, radiology, and predictive analytics, offering improved accuracy and efficiency in clinical decision-making. 1 However, these advancements also pose significant ethical, regulatory, and bias-related concerns that require careful consideration to ensure equitable and safe implementation.